Sustainable competitive advantage (sca) analysis of furniture manufacturers in malaysia: normalized scaled critical factor index (NSCFI) approach - Tasmin, Rosmaini; Takala, Josu; Abu Bakr, Aliyu Alhaji; Shylina, Daryna; Nizialek, Izabela; Che Rusuli, M.S. (Polish Academy of Sciences, 2016)
The purpose of this paper is to investigate Malaysian furniture industry via Sustainable competitive advantages (SCA) approach. In this case study, sense and respond method and Normalized Scaled Critical Factor Index (NSCFI) are used to specify the distribution of companies’ resources for different criteria and detect the attributes which are critical based on expectation and experience of companies’ employs. Moreover, this study evaluates Malaysian furniture business strategy according to manufacturing strategy in terms of an-alyzer, prospector and defender. Finally, SCA risk levels are presented to show how much company’s resource allocations support their business strategy. This case study involved four furniture manufacturing companies, in the southern part of Peninsular Malaysia to provide the overall view of their strategies in the perspective of knowledge & technology management, processes & work flows, organizational, and informa-tion systems. Hence, the findings of this study presented the preliminary results from these furniture companies in Malaysia, which are involved in sustainable competitive advantage (SCA) studies in terms of expectation and experience, NSCFI, operational strategy triangle of prospector (P), defender (D), and analyzer (A). The result shows that almost all fur-niture companies are categorized into the Analyzer type strategy and planning to remain being Analyzer in future to come.